How older adults use cognition in sentence-final word recognition. Issue 4 (3rd July 2016) - Cahana-Amitay, Dalia; Spiro, Avron; Sayers, Jesse T.; Oveis, Abigail C.; Higby, Eve; Ojo, Emmanuel A.; Duncan, Susan; Goral, Mira; Hyun, Jungmoon; Albert, Martin L.; Obler, Loraine K.
ABSTRACT: This study examined the effects of executive control and working memory on older adults' sentence-final word recognition. The question we addressed was the importance of executive functions to this process and how it is modulated by the predictability of the speech material. To this end, we tested 173 neurologically intact adult native English speakers aged 55–84 years. Participants were given a sentence-final word recognition test in which sentential context was manipulated and sentences were presented in different levels of babble, and multiple tests of executive functioning assessing inhibition, shifting, and efficient access to long-term memory, as well as working memory. Using a generalized linear mixed model, we found that better inhibition was associated with higher accuracy in word recognition, while increased age and greater hearing loss were associated with poorer performance. Findings are discussed in the framework of semantic control and are interpreted as supporting a theoretical view of executive control which emphasizes functional diversity among executive components.